TRANSFORMASI PRAKTIK JURNALISTIK DI ERA DIGITAL:: STUDI DESKRIPTIF TENTANG ADAPTASI MEDIA DARING DI SURABAYA - Wisnumurti, Rafael Zahirul Haq Haryo (Universitas 17 Agustus 1945 Surabaya, 2025)
This research aims to describe the transformation of journalistic practices in the digital era in online media in Surabaya. The digital age has brought fundamental changes in the production, distribution, and consumption of news, forcing the media to adapt. This qualitative descriptive study explores how online media in Surabaya responds to these changes through in-depth interviews with key players in the online media industry and analysis of media content documents. The findings of the study show a significant transformation in various aspects of journalistic practice. In content production, Surabaya's online media adopts a multimedia format and a faster and more collaborative workflow. Engagement with audiences is enhanced through comment sections, social media, and online surveys. The media business model is also transforming with the exploration of digital advertising, sponsored content, and the potential of community-based models. However, Surabaya's online media also faces challenges such as fierce competition, the need to maintain accuracy in the midst of speed, and disinformation issues. Various adaptation strategies were identified, including a focus on hyper-local content, increased verification, and diversification of revenue models. This study concludes that online media in Surabaya is actively transforming to respond to the digital era, although challenges remain. This adaptation is important for the sustainability and relevance of the media in serving the information needs of local communities. This study provides insight into the dynamics of the evolution of journalism at the local level in a digital context. Keyword: Journalistic Transformation, Online Media, Media Adaptation, Descriptive Study.